Coping With Dating Violence as a Function of Violence Frequency and Solution Attribution: A Structural Modeling Approach. - Bapat, Mona; Tracey, Terence J. G. (Violence & Victims, 2012)
This study presents a structural model of coping with dating violence. The model inte-grates abuse frequency and solution attribution to relate to college women's choices of coping strategies. Three hundred and twenty-four undergraduate women reported being targets of some physical abuse from a boyfriend and responded to questions regarding the abuse, their solution attribution, and their coping behaviors. Solution attribution mediated the relation between frequency of the abuse and coping. Abuse frequency had a positive effect on external solution attribution, and external solution attribution had a positive effect on the level of use of active coping, utilization of social support, denial, and acceptance.